2021
DOI: 10.1177/10105395211048620
|View full text |Cite|
|
Sign up to set email alerts
|

Developing a Predictive Model for Plasmodium knowlesi–Susceptible Areas in Malaysia Using Geospatial Data and Artificial Neural Networks

Abstract: Plasmodium knowlesi is an emerging species for malaria in Malaysia, particularly in East Malaysia. This infection contributes to almost half of all malaria cases and deaths in Malaysia and poses a challenge in eradicating malaria. The aim of this study was to develop a predictive model for P. knowlesi susceptibility areas in Sabah, Malaysia, using geospatial data and artificial neural networks (ANNs). Weekly malaria cases from 2013 to 2014 were used to identify the malaria hotspot areas. The association of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Molecular epidemiological studies have found that the geographical separation could have also driven the allopatric divergence of P. knowlesi into distinct subpopulations ( Divis et al, 2017 ). Studies in Sabah, a state in Malaysian Borneo, have demonstrated the association between environmental factors and knowlesi malaria risk ( Brock et al, 2019 ; Fornace et al, 2019 ; Sato et al, 2019 ; Hod et al, 2022 ). However, environmental influences on knowlesi malaria in Peninsular Malaysia are not widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular epidemiological studies have found that the geographical separation could have also driven the allopatric divergence of P. knowlesi into distinct subpopulations ( Divis et al, 2017 ). Studies in Sabah, a state in Malaysian Borneo, have demonstrated the association between environmental factors and knowlesi malaria risk ( Brock et al, 2019 ; Fornace et al, 2019 ; Sato et al, 2019 ; Hod et al, 2022 ). However, environmental influences on knowlesi malaria in Peninsular Malaysia are not widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…There are several existing spatial distribution models of P. knowlesi malaria risk [ 9 , 36 , 37 ]. While other models predict P. knowlesi malaria risk on a district or state level, a key distinction of the model described by Shearer et al [ 9 ] is a map with a resolution of approximately 5 × 5 km 2 of relative predicted risk throughout the Southeast Asia region [ 9 ] (electronic supplementary material, §S2).…”
Section: Methodsmentioning
confidence: 99%
“…The simian parasite Plasmodium knowlesi with a natural reservoir in long-tailed macaques, pig-tailed macaques and banded leaf monkeysis considered the fth Plasmodium species causing malaria in humans (1,2). P. knowlesi cases have been reported from almost every country in Southeast Asia, but the Malaysian states of Sarawak and Sabah have the highest incidence in the region (3), where it is an emerging challenge in efforts to eliminate malaria (4). No indigenous cases of Plasmodium falciparum, Plasmodium vivax or Plasmodium malariae have been recorded in Malaysia since 2017, and in 2020, the country reached the World Health Organization Global Technical Strategy for Malaria 2016-2030 goal by interrupting local malaria transmission (5).…”
Section: Introductionmentioning
confidence: 99%